1977
DOI: 10.1016/0035-9203(77)90211-5
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure distribution in a rural Ghanaian population

Abstract: Hypertension and related complications appear, from clinical impression, to be increasing problems in urban Ghanaians. In early 1973 we conducted a blood pressure survey in 20 rural Ghanaian villages to determine the prevalence of hypertension, in comparison with studies done in Accra residents and black Americans. Rural Ghanaians had mean systolic and diastolic blood pressures which were lower at all ages than the urban groups. 2-5% of the subjects aged 16 to 54 years had diastolic blood pressures of 95 or hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
47
1

Year Published

1984
1984
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 8 publications
0
47
1
Order By: Relevance
“…Among the urban dwellers, 24% knew they were hypertensive and 7.2% were on some form of treatment, though only half were being treated adequately. 4,9,28 More recently, in Accra, Amoah found overall crude and age-standardized prevalence rates of hypertension (BP Ն140/90 mm Hg) to be 28.3% and 27.3%, respectively. 10 Hypertension was more common in women than men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the urban dwellers, 24% knew they were hypertensive and 7.2% were on some form of treatment, though only half were being treated adequately. 4,9,28 More recently, in Accra, Amoah found overall crude and age-standardized prevalence rates of hypertension (BP Ն140/90 mm Hg) to be 28.3% and 27.3%, respectively. 10 Hypertension was more common in women than men.…”
Section: Discussionmentioning
confidence: 99%
“…2 In a recent study, the prevalence of hypertension was found to be 28% in North America and 44% in western Europe. 1 Until recently, hypertension was thought to be rare in rural Africa [3][4] ; on the other hand, hypertension and its complications, including stroke, heart failure, and renal failure, have been reported in blacks all over the world. Hypertension is now being widely reported in Africa and is the most common cause of cardiovascular disease on the continent.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Some had been based on community surveys 1,[3][4][5][6]11 and others on particular sectors of the population. 2,[7][8][9][10] However, there are few reports of revisits to cities, towns or villages to study time changes in blood pressure (BP).…”
Section: Introductionmentioning
confidence: 99%
“…Studies suggest that the prevalence of hypertension is higher in urban than rural areas. [7][8][9] Increasing urbanisation in West Africa is associated with an increasing prevalence of hypertension 9 so the burden of hypertension and its related complications on morbidity and mortality will rise. Indeed, hypertensive renal damage is the main cause of end-stage renal failure in black populations both in the UK 10 and in West Africa.…”
Section: Introductionmentioning
confidence: 99%